2021
DOI: 10.1590/1414-431x202010152
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic markers in pediatric septic shock prognosis: an integrative analysis of gene expression profiles

Abstract: The goal of this study was to identify potential transcriptomic markers in pediatric septic shock prognosis by an integrative analysis of multiple public microarray datasets. Using the R software and bioconductor packages, we performed a statistical analysis to identify differentially expressed (DE) genes in pediatric septic shock non-survivors, and further performed functional interpretation (enrichment analysis and co-expression network construction) and classification quality evaluation of the DE genes iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Obesity paradoxically exhibits an association with improved mortality outcomes in sepsis when compared with leaner patients (1,2). This phenomenon, known as the obesity paradox, has been discussed previously (3,4). However, it is important to note that the protective effect of obesity in sepsis remains a topic of debate (5).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Obesity paradoxically exhibits an association with improved mortality outcomes in sepsis when compared with leaner patients (1,2). This phenomenon, known as the obesity paradox, has been discussed previously (3,4). However, it is important to note that the protective effect of obesity in sepsis remains a topic of debate (5).…”
Section: Introductionmentioning
confidence: 78%
“…Epidemiological data indicate that individuals with obesity exhibit a heightened likelihood of survival during clinical systemic inflammatory responses ( 1 , 2 ). This intriguing phenomenon is commonly referred to as the ‘obesity paradox’ ( 3 , 4 , 6 , 38 ), yet the actual protective mechanisms in the context of sepsis continue to be a subject of debate ( 5 ). An essential factor to consider in this analysis is the programming process during the intrauterine and lactation period, as per the Developmental Origins of Health and Disease (DOHaD) concept.…”
Section: Discussionmentioning
confidence: 99%
“…As in our rat model, recent studies agreed on a modification of the gene expression profile during sepsis in the young. The DNA Damage Inducible Transcript 4 ( Ddit4 ), a gene associated with higher risks of mortality, has notably been identified as overexpressed in the young with septic shock [ 49 , 50 , 51 ]. Animal septic shock models have been largely used over the past decades to better understand pathophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also taken advantage of microarray datasets for septic shock biomarker analysis, from which they found that 32 DEGs were associated with pediatric septic shock characterized by a fatal outcome, with OLFM4 as the most significantly upregulated gene and MME as the most significantly downregulated one. 74 A few studies specifically focused on the screening of lncR-NAs and miRNAs as diagnostic biomarkers in pediatric sepsis. For example, Wu et al 75 revealed that the lncRNAs THAP9-AS1 and TSPOAP1-AS1 may help in the differentiation of septic shock samples from control samples.…”
Section: Biomarkers Screened By Transcriptomicsmentioning
confidence: 99%
“…Researchers have also taken advantage of microarray datasets for septic shock biomarker analysis, from which they found that 32 DEGs were associated with pediatric septic shock characterized by a fatal outcome, with OLFM4 as the most significantly upregulated gene and MME as the most significantly downregulated one. 74 …”
Section: Biomarkers Screened By Transcriptomicsmentioning
confidence: 99%